2008
DOI: 10.1037/0893-164x.22.1.141
|View full text |Cite
|
Sign up to set email alerts
|

Live interactive group-specific normative feedback reduces misperceptions and drinking in college students: A randomized cluster trial.

Abstract: This research evaluated the efficacy of a live and interactive group-specific normative feedback intervention designed to correct misperceptions of alcohol-related group norms and subsequently reduce drinking behavior. Campus organizations (N = 20) containing 1,162 college students were randomly assigned to intervention or assessment-only control conditions. Participants in the intervention condition attended an intervention during their organization's regular standing meeting. Data were gathered in vivo using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 30 publications
4
79
0
Order By: Relevance
“…Personalized normative feedback alone has also been shown to measurably reduce drinking among heavy drinkers for up to 2 years (Neighbors et al, , 2010. Group-based live interactive norms feedback has also been effective in reducing groupspecifi c normative misperceptions and subsequent drinking (Killos et al, 2010;LaBrie et al, 2008). The present results suggest that incorporation of content related to religious values may be a useful addition to existing intervention approaches, particularly with individuals whose current drinking behavior is discrepant from their religious values.…”
Section: Discussionmentioning
confidence: 74%
“…Personalized normative feedback alone has also been shown to measurably reduce drinking among heavy drinkers for up to 2 years (Neighbors et al, , 2010. Group-based live interactive norms feedback has also been effective in reducing groupspecifi c normative misperceptions and subsequent drinking (Killos et al, 2010;LaBrie et al, 2008). The present results suggest that incorporation of content related to religious values may be a useful addition to existing intervention approaches, particularly with individuals whose current drinking behavior is discrepant from their religious values.…”
Section: Discussionmentioning
confidence: 74%
“…Recent research by LaBrie and colleagues indicates realtime normative feedback provided to group members using in-person interactive polling is associated with reduced group-specifi c normative misperceptions and subsequent drinking among fraternity/sorority members in addition to services-group members (LaBrie et al, 2008) and athletes (LaBrie et al, 2009). Future research could evaluate the extent to which effects of group-specifi c feedback are maintained over time or in different implementation formats (i.e., Web, mailed).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, interventions have targeted group-specifi c normative misperceptions, including gender-specifi c norms Neighbors, 2004, 2007;Thombs et al, 2005), freshman-specifi c norms , and fraternity/sorority-specifi c norms (LaBrie et al, 2008). These efforts demonstrated that group-specifi c perceptions infl uence individuals' behavior, and thus, targeting these norms can assist in reducing drinking.…”
Section: Specifi City Of the Normative Referent Groupmentioning
confidence: 99%
“…Research has shown that fraternity membership is a strong predictor of frequency of heavy drinking (Wechsler et al, 1995) for both alcohol-experienced and alcohol-naive beginning college students (Lo and Globetti, 1995). Overestimations of fraternity/sorority-specifi c drinking have been documented and have been shown to associate with individual drinking rates (Bartholow et al, 2003;Larimer et al, 1997Larimer et al, , 2004, and correction of fraternity/sorority-specifi c perceived norms have mediated reductions in drinking during intervention (LaBrie et al, 2008).…”
Section: Specifi City Of the Normative Referent Groupmentioning
confidence: 99%
See 1 more Smart Citation